STUDI KARAKTERISTIK BRIKET ARANG BIOMASSA BERBASIS SCREW PRESS - Dahlan, Masbin; Sulfiana, Enni; purna yudha, sabdha; Amaluddin, Muh. Nurul Haq (Jurnal Rekayasa Mesin, 2024)
Biomass is material originating from plants that can be used as a source of energy, fuel, or a substitute for products and materials originating from fossils. One of the raw materials for biomass briquettes, an energy alternative, is coconut shells. To increase briquette production and simplify the process, briquette-making machine tools or technology are needed that can be used for large-quantity production. This research aims to design and build a biomass charcoal briquette densification machine using the Screw Press system, as well as test the performance of the densification machine in making biomass charcoal briquettes from coconut shells using tapioca adhesive and kapok leaf extract. The motor power required for the charcoal briquette densification machine is 2.33 PK. This densification machine is capable of producing charcoal briquettes weighing 11,115 grams per minute or 667 kg per hour with a rotation speed of 350 rpm. The average performance efficiency of the densification machine reached 98.33%. The average density of briquettes using tapioca flour adhesive is 0.9941 g/cm3, while for briquettes using kapok leaf extract, it is 0.9579 g/cm3. The drop test results showed an average value of 0.1133% for each type of briquette. The average briquette compression test values were 2.6133 N/mm2 and 2.0733 N/mm2, while the average ash content was 2.94% and 3.20%. The average burning rate of briquettes is 0.1112 g/minute and 0.1273 g/minute for each type of briquette.